2015
DOI: 10.1021/es504529x
|View full text |Cite
|
Sign up to set email alerts
|

Can China Comply with Its 12th Five-Year Plan on Industrial Emissions Control: A Structural Decomposition Analysis

Abstract: China's rapid economic growth has caused serious environmental problems, resulting in the implementation of two major measures-end-of-pipe facilities and the phasing out of backward capacity-to reduce China's industrial emissions as part of its 11th Five-Year Plan (FYP, 2006-2010). It is important to determine whether China can meet the targets set forth in its 12th FYP (2011-2015) for industrial pollution reduction using these same solutions. In this paper, structural decomposition analysis (SDA) was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Due to the highest proportional output and energy consumption for the industry, a decrease in the energy consumption per unit of output in the industry would lead to substantial air pollutants emissions reduction, which is supported by [62]. It is worth mentioning that, during 2007-2012, the energy intensity effect on the inhibition of air pollutants showed a downward trend.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Due to the highest proportional output and energy consumption for the industry, a decrease in the energy consumption per unit of output in the industry would lead to substantial air pollutants emissions reduction, which is supported by [62]. It is worth mentioning that, during 2007-2012, the energy intensity effect on the inhibition of air pollutants showed a downward trend.…”
Section: Discussionmentioning
confidence: 84%
“…In recent studies, Zhang et al analyzed drivers of fossil fuel use and air pollutant emissions in Beijing during 1997-2010 from both bottom-up and top-down perspectives, based on the SDA method, and the results showed that the key energy-intensive industrial sectors directly caused the variations in Beijing's air pollution, and population growth was the largest driver of energy consumption and air pollutant emissions [61]. Zhang et al applied the SDA method to decompose the changes of industrial pollutant emissions into the effects of end-of-pipe abatement efficiency, pollutant generation intensity, production structure, final demand structure, final demand composition, and total final demand, and evaluated the feasibility of the reduction target in China's 12th Five-Year Plan period [62]. Liu and Wang applied the SDA method to decompose the factors on the changes of industrial SO 2 emissions and chemical oxygen demand into the pollution abatement, pollutant generation coefficient, production structure, final import coefficient, exports, and domestic final demands effects, and discussed how China achieved its 11th Five-Year Plan emissions reduction target [63].…”
Section: Introductionmentioning
confidence: 99%
“…A much more substantial update came with version V5a where for China the 12th Five-Year Plan policies were introduced, resulting in revision of the implementation and enforcement rates of control measures for 2010, drawing also on analysis of progress in legislation implementation in China (e.g. Lin et al, 2010;Zhang et al, 2015). Furthermore, the legislation for the cement industry was reviewed and updated (Edwards, 2014), emissions from international shipping were also calculated, and the treatment of non-road mobile machines was reviewed; in addition, for Latin America and Caribbean (LAC) the GAINS model has been revised to include nearly all single countries 6 and, consequently, required definition of control strategies reflecting current legislation for each country.…”
Section: Emission Legislationmentioning
confidence: 99%
“…China's energy intensity had been declining for a long time, especially in the industrial sector [65]. For the high output and fossil energy consumption in the industrial sector, decreases in energy use per unit output in the industry resulted in significant decreases in APEs, and decreases in energy use per unit output in the industry resulted in significant decreases in APEs, and this result was supported by Zhang et al (2015) [66]. During the study period, the degree of curbing the effect of regional energy intensity declined, which reflects the dropping trend of promotion of China's industrial energy efficiency.…”
Section: The Regional Energy Intensity Effect Curbed Apesmentioning
confidence: 89%